Avoidance threshold to oil water‐soluble fraction by a juvenile marine teleost fish. (30th December 2017) - Claireaux, Guy; Quéau, Pierre; Marras, Stefano; Le Floch, Stéphane; Farrell, Anthony P.; Nicolas‐Kopec, Annabelle; Lemaire, Philippe; Domenici, Paolo
Abstract: When oil spills occur, behavior is the first line of defense for a fish to avoid being contaminated. We determined the avoidance threshold of the European seabass ( Dicentrarchus labrax ) to the water‐soluble fraction (WSF) of oil using a dual‐flow choice box. The results showed that a plume of 20%‐diluted WSF (total polycyclic aromatic hydrocarbon [PAH] concentration: 8.54 μg L −1 ) triggered a significant avoidance response that was detected within 7.5 min of introducing WSF‐contaminated water into the experimental setup. However, the ecological relevance of seabass capacity to detect and avoid WSF remains to be established. In the short term, such a response is indeed liable to reduce seabass contact time with oil‐contaminated water and thus preserve their functional integrity. In the long term, however, avoidance may contribute to the displacement of a population into a possibly less auspicious environment, with consequences very similar to those of contaminant exposure, that is, disturbed population dynamics and demography. Environ Toxicol Chem 2018;37:854–859. © 2017 SETAC